Operational Determination of Subjective Cognitive Decline, Mild Cognitive Impairment, and Dementia Using Sum of Boxes of the Clinical Dementia Rating Scale - Yang, Yu-Wan; Hsu, Kai-Cheng; Wei, Cheng-Yu; Tzeng, Ray-Chang; Chiu, Pai-Yi (Frontiers in Aging Neuroscience, 2021)
Objectives: The Clinical Dementia Rating (CDR) scale is the gold standard for the staging of dementia due to Alzheimer’s disease (AD). However, the application of CDR for the staging of subjective cognitive decline (SCD) and mild cognitive impairment (MCI) in AD remains controversial. This study aimed to use the sum of boxes of the CDR (CDR-SB) plus an SCD single questionnaire to operationally determine the different stages of cognitive impairment (CI) due to AD and non-AD. Methods: This was a two-phase study, and we retrospectively analyzed the Show Chwan Dementia registry database using data selected from 2015 to 2020. Individuals with normal cognition (NC), SCD, MCI, and mild dementia due to AD or non-AD with a CDR < 2 were included in the analysis. Results: A total of 6946 individuals were studied, including 875, 1009, 1585, and 3447 with NC, SCD, MCI, and mild dementia, respectively. The cutoff scores of CDR-SB for NC/SCD, SCD/MCI, and MCI/dementia were 0/0.5, 0.5/1.0, and 2.5/3.0, respectively. The receiver-operating characteristic (ROC) analysis showed that the test groups’ area under the curve was 0.85, 0.90, and 0.92 for discriminating NC from SCD, SCD from MCI, and MCI from dementia, respectively. Compared with the Cognitive Abilities Screening Instrument or the Montreal Cognitive Assessment, using CDR-SB is less influenced by age and education. Conclusions: Our study showed that the operational determination of SCD, MCI, and dementia using the CDR-SB is practical and can be applied in clinical settings and research on CI or dementia.